VERTICAL DISTRIBUTION OF NUTRIENTS IN GROUNDNUT GROWING SOILS IN SEMIARID REGION OF VARATHURU WATERSHED IN CHITTOOR DISTRICT - G.P. LEELAVATHY, M.V.S. NAIDU*, T. GIRIDHARA KRISHNA, K.V. RAMANA, V. CHANDRIKA and P. SUDHAKAR (The Journal of Research ANGRAU, 2021)
The land survey was undertaken to study the vertical distribution of plant nutrients in the soilprofiles/ pedons in groundnut growing areas of Varathuru watershed in Chittoor district to understandnutrient supply capacity of soils. The results revealed that plant available P and K in these soils weresufficient in the surface and subsurface horizons of all pedons except pedon 2 , wherein, P wasdeficient in the subsurface horizon. Exchangeable Ca and Mg and available S were sufficient insurface and subsurface soils of all pedons except pedon 3 wherein S was deficient in surface horizon.The available S and exchangeable Ca and Mg in pedons 1 and 4 were high in surface horizons thanin subsurface horizons and pedons 2, 3 and 5 showed an inconsistent trend with depth. The DTPAextractableCu and Mn in these soils were found to be above critical limits in surface and subsurfacehorizons in all the pedons except in pedons 1 and 5 for Cu in subsurface horizons and Mn in surfacehorizon in pedon 4. The available Zn was deficient in all the pedons except pedons 2 and 5 in surfacehorizons and the available Fe was found to be above critical limits in surface horizons in all thepedons and below critical limit in subsurface horizons in pedons 2 and 4. All the micronutrients werehigher in surface soils than for subsurface soils except in pedon 5 for Zn and Cu, pedons 1 and 5 forFe and pedon 3 for Mn.